Correction: Boosting the activity of catalytic oxidation of 5-hydroxymethylfurfural to 2, 5-diformylfuran over nitrogen-doped manganese oxide catalysts. Issue 13 (18th June 2019) - Ke, Qingping; Jin, Yangxin; Ruan, Fei; Ha, Minh Ngoc; Li, Dandan; Cui, Peixin; Cao, Yali; Wang, Hao; Wang, Tongtong; Nguyen, Van Noi; Han, Xinya; Wang, Xi; et al.
Abstract : Correction for 'Boosting the activity of catalytic oxidation of 5-hydroxymethylfurfural to 2, 5-diformylfuran over nitrogen-doped manganese oxide catalysts' by Qingping Ke et al., Green Chem., 2019, DOI: 10.1039/c9gc01041f.